Design and Synthesis of New Etodolac‐Pyridazinones as Potent Anticancer Agents Using Pb(OAc)4 to Assist N‐N Bond Formation. Issue 18 (9th May 2018) - Kummari, Bhaskar; Ramesh, Perla; Parsharamulu, Rayam; Allaka, Tejeswara Rao; Anantaraju, Hasithashilpa; Yogeeswari, Perumal; Balasubramanian, Sridhar; Guggilapu, Sravanthi Devi; Babu, Bathini Nagendra; Anireddy, Jaya Shree
Abstract: Pb(OAc)4 to assist N−N bond formation via dehydrogenative cyclization of hydrazide‐hydrazones to generate the pyridazinones as bioactive molecules have been described. All the products were well characterized by various spectroscopic analyses. Furthermore, the structure of ( E )‐3a, 7‐diethyl‐6‐((thiophen‐2‐ylmethylene)amino)‐1, 2, 3a, 4‐tetrahydro‐3‐oxa‐6, 6a‐diazafluoranthen‐5(6H)‐one was unambiguously conformed by single crystal X‐ray analysis. The in vitro biological evaluation revealed that several of these compounds exhibited greater cytotoxic potency than that of doxorubicin drug. ( E )‐N′‐(4‐chlorobenzylidene)‐2‐(1, 8‐diethyl‐1, 3, 4, 9‐tetrahydropyrano[3, 4‐b]indol‐1‐yl)acetohydrazide exhibited most cytotoxic activity against both A549 and PC3 cancer cell lines with IC50 values of 1.77±0.08 and 1.88±0.33 μM, respectively. Abstract : Pb(OAc)4 to assist N−N bond formation via dehydrogenative cyclization of etodolac‐hydrazide‐hydrazones to generate the etodolac‐pyridazinones as bioactive molecules have been described. The in vitro biological evaluation revealed that several of these compounds exhibited greater cytotoxic potency than that of doxorubicin drug. Importantly, the compound ( E )‐N′‐(4‐chlorobenzylidene)‐2‐(1, 8‐diethyl‐1, 3, 4, 9‐tetrahydropyrano[3, 4‐b]indol‐1‐yl)acetohydrazide showed most cytotoxic activity against both A549 and PC3 cancer cell lines with IC50 values of 1.77±0.08 and 1.88±0.33 μM, respectively.